Frequency and Pattern of Metastases in Treated Breast Cancer Patients Detected on 18F-FDG PET-CT: One Year Experience at INMAS Mohakhali - Bhattacharjee, Puja; Sharmin, Rahima Akter; Hossain, Arshad; Parveen, Rumana; Yasmeen, Nilufa; Zaman, Mahbuba; Alam, Md Jahir; Kabir, Md Alamgir; Khan, Md Shahidul Islam; Quddus, Sharmin; Chakma, Rubel (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Breast cancer is one of the most common malignancies among women worldwide. Early detection of recurrence and metastatic disease is crucial for optimal management. 18F-FDG PET-CT plays an important role in evaluating treated breast cancer patients. Objective: To determine the frequency and pattern of metastases in treated breast cancer patients using FDG PET-CT. Methods: This retrospective observational study included 94 treated breast cancer patients who underwent FDG PET-CT over a period of one year at the Institution of Nuclear Medicine and Allied Sciences, Mohakhali, Dhaka. The presence, sites, and patterns of metastases were analyzed. Results: Out of 94 patients, metastatic disease was detected in 36 patients (38.3%), while 58 patients (61.7%) showed no evidence of metastasis. Multiple site metastases were more common (61.1%) than single-site metastases (38.9%). The most common site of metastasis was lymph nodes (66.7%), followed by bone (61.1%), liver (27.8%), and lung (16.7%). Less common sites included the ovary (5.6%) and contralateral breast (5.6%). Mixed-pattern metastases were the most frequent presentation (61.1%). Conclusion: 18F-FDG PET-CT is a valuable imaging modality for detecting metastatic disease in treated breast cancer patients, with nodal and skeletal metastases being the most common. Mixed pattern involvement is frequently observed. Thus, PET-CT plays a vital role in the evaluation of metastases, guiding further treatment decisions and management. Bangladesh J. Nuclear Med. 29(1): 36-42, 2026